2020
DOI: 10.1111/ans.15686
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term incidence of dysplasia and colorectal cancer in an ulcerative colitis population‐based cohort

Abstract: Background: Ulcerative colitis (UC) is a risk factor in developing colorectal cancer (CRC). Surveillance programmes aim to identify premalignant lesions to facilitate improved treatment outcomes. Recent studies have suggested that the risk of CRC in UC has decreased. This study aims to characterize the risk of CRC in UC in a population-based New Zealand cohort. Methods: All patients in the Canterbury Inflammatory Bowel Disease Study, a comprehensive population-based cohort, were reviewed and cases of dysplasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…4 Other studies have shown a standardized incidence ratio (SIR) of around 1.8, increasing to between 3 and 4 with extensive disease. 4 16 17 In CD, the risk is appreciable only if the colonic phenotype is considered as opposed to the non-colonic phenotypes. In this subgroup, the risk is comparable to the UC population with an SIR over 4 in some studies.…”
Section: Epidemiologymentioning
confidence: 99%
“…4 Other studies have shown a standardized incidence ratio (SIR) of around 1.8, increasing to between 3 and 4 with extensive disease. 4 16 17 In CD, the risk is appreciable only if the colonic phenotype is considered as opposed to the non-colonic phenotypes. In this subgroup, the risk is comparable to the UC population with an SIR over 4 in some studies.…”
Section: Epidemiologymentioning
confidence: 99%
“…The incidence of colorectal cancer is increasing, and UC is a risk factor of colorectal cancer (2,3). Despite advances in therapeutic options, in a cohort study conducted in New Zealand between 2005 and 2015, 2.7% of all patients with UC went onto develop colorectal cancer (4). UC has a marked negative impact on the quality of life of the patients.…”
Section: Introductionmentioning
confidence: 99%